2011
DOI: 10.1042/bst0391067
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria in the pathogenesis of inflammatory bowel disease

Abstract: Twin studies have demonstrated the importance of environmental factors in the pathogenesis of inflammatory bowel disease, but progress has been relatively slow in identifying these, with the exception of smoking, which is positively associated with Crohn's disease and negatively associated with ulcerative colitis. Genetic studies have identified risk alleles which are involved in host-bacterial interactions and the mucosal barrier, and evidence is building for a likely pathogenic role for changes in the gut mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 66 publications
(67 reference statements)
1
30
1
Order By: Relevance
“…However, genetic, phenotyping, and microbial diversity within UC patients indicate that this disease is the heterogeneous cohort of different disorders, which probably has predictable natural histories (23). However, recent studies demonstrated that Entrobacteriaceae, E. coli, and Mycobacterium paratuberculosis strains are associated with IBD (24). The current study showed that there was a higher rate of fimH gene in UC patients than control subjects; a difference that was statistically significant.…”
Section: Discussioncontrasting
confidence: 44%
“…However, genetic, phenotyping, and microbial diversity within UC patients indicate that this disease is the heterogeneous cohort of different disorders, which probably has predictable natural histories (23). However, recent studies demonstrated that Entrobacteriaceae, E. coli, and Mycobacterium paratuberculosis strains are associated with IBD (24). The current study showed that there was a higher rate of fimH gene in UC patients than control subjects; a difference that was statistically significant.…”
Section: Discussioncontrasting
confidence: 44%
“…Mycobacterium avium spp. paratuberculosis or adherent-invasive Escherichia coli (AIEC)) have been proposed as causative agents, mainly in CD [138][139][140]. Moreover, various clinical studies were conducted to analyze the potential therapeutic effect of different antibacterial regimens (usually with the agents clarithromycin, metronidazole, ciprofloxacin or rifaximin) (see section 3.4.…”
Section: The Microbiotamentioning
confidence: 99%
“…Moreover, a defective mucus layer has been associated with UC in humans and colitis in mice [40,80,81]. Additionally, an increased number of epithelium-associated bacteria have been found in IBD, although more consistently in CD than UC [82,83]. Finally, our pharmacogenetics studies of gene-environment interactions in relation to development of colorectal cancer, suggest that intake of red and processed meat interacts with genes encoding TLRs and NF-κB [84], which may offer a potential link to anti-TNF treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that plant fibre may be important for restoring the mucus layer [40,82]. Supplementation with complex oligosaccharides such as those present in soluble edible plant fibres was able to inhibit the adherence of pathogen bacteria to epithelial cells in a hen model [73].…”
Section: Discussionmentioning
confidence: 99%